Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude